2015
DOI: 10.1093/mnras/stv2052
|View full text |Cite
|
Sign up to set email alerts
|

Preserving chemical signatures of primordial star formation in the first low-mass stars

Abstract: We model early star forming regions and their chemical enrichment by Population III (Pop III) supernovae with nucleosynthetic yields featuring high [C/Fe] ratios and pair-instability supernova (PISN) signatures. We aim to test how well these chemical abundance signatures are preserved in the gas prior to forming the first long-lived low-mass stars (or second-generation stars). Our results show that second-generation stars can retain the nucleosynthetic signature of their Pop III progenitors, even in the presen… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
86
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 78 publications
(95 citation statements)
references
References 119 publications
(198 reference statements)
9
86
0
Order By: Relevance
“…This CEMP fraction (83%) is somewhat higher than the halo (Placco et al 2014) but is consistent with expectations for UFDs (Salvadori et al 2015). Besides carbon, TucII-011 differs from the TucII CEMP-no stars in having especially low neutron-capture element abundances [Fe/H]−3, this could suggest that PopIII stars produce at least two distinct types of yields (e.g., Cooke & Madau 2014;Ji et al 2015; and in contrast to, e.g., Salvadori et al 2015). An interesting alternate scenario is if different metals created from a single source were to mix differently into the surrounding gas (Sluder et al 2016).…”
Section: Popiii Signatures In Tucanaiisupporting
confidence: 85%
See 1 more Smart Citation
“…This CEMP fraction (83%) is somewhat higher than the halo (Placco et al 2014) but is consistent with expectations for UFDs (Salvadori et al 2015). Besides carbon, TucII-011 differs from the TucII CEMP-no stars in having especially low neutron-capture element abundances [Fe/H]−3, this could suggest that PopIII stars produce at least two distinct types of yields (e.g., Cooke & Madau 2014;Ji et al 2015; and in contrast to, e.g., Salvadori et al 2015). An interesting alternate scenario is if different metals created from a single source were to mix differently into the surrounding gas (Sluder et al 2016).…”
Section: Popiii Signatures In Tucanaiisupporting
confidence: 85%
“…The abundances of these metal-poor stars likely trace the nucleosynthetic output of the first PopulationIII (Pop III) stars that enriched their host galaxy. Since UFDs have relatively simple star formation histories, they are a particularly powerful probe for dwarf galaxy archaeology, as all their stars formed from the same galactic environment (e.g., Frebel & Bromm 2012;Karlsson et al 2013;Ji et al 2015). This provides valuable constraints on the nature and site of the first nucleosynthesis events that cannot be derived for field stars from the chemical signatures alone (e.g., Ji et al 2016a).…”
Section: Introductionmentioning
confidence: 99%
“…The small number of enriching stellar generations and the simple environment suggests that UFDs are one of the best places to find chemical signatures from the first generation of stars (Frebel & Bromm 2012;Karlsson et al 2013;Ji et al 2015). One of the most promising signatures is the increasing fraction of carbon-enhanced metal-poor (CEMP) stars at low metallicity, which may be associated with the initial mass function of PopIII stars (e.g., Norris et al 2013;Cooke & Madau 2014).…”
Section: Signatures Of the First Starsmentioning
confidence: 99%
“…Frebel & Bromm (2012) suggest that the chemical signatures of low-mass ultrafaint dwarfs can be described by a single, longlived generation of stars that formed in the early universe. In related work, Ji et al (2015) demonstrate that the chemical abundance patterns of these single events can be preserved in the second generation of stars. Though Hor I does not have the characteristically high α-element abundance predicted by Frebel & Bromm (2012) in their "one-shot enrichment" scenario, if Aoki et al (2014) are correct that their observed abundance patterns, which are similar to ours, are due to a PISN, then we expect that there must have been only a single nucleosynthetic event in Hor I.…”
Section: Comparison To Supernova Yield Modelsmentioning
confidence: 90%
“…Star formation in these low-mass objects is likely to be highly influenced by only a few nucleosynthetic events (e.g., Ji et al 2015). And since star formation in ultrafaint dwarfs appears to have been quenched early in the history of the universe, perhaps by reionization (Brown et al 2014;Wetzel et al 2015;Jeon et al 2017), a fossil record of the early star formation history of these objects is preserved today.…”
Section: Introductionmentioning
confidence: 99%